Razvojni pomen nepremične kulturne dediščine v lokalnih okoljih – prepoznavanje moči dejavnikov novega lokalizma in elementov nepremične kulturne dediščine za ohranjanje kakovosti življenja - Uršič, Matjaž (Dela - Oddelek za geografijo Filozofske fakultete v Ljubljani, 2025)
Immovable cultural heritage represents a key spatial and symbolic value for local communities, yet numerous examples indicate its limited integration into the con-temporary needs of residents. This article analyses how the approaches of new lo-calism—as a conceptual framework combining local specificities with responses to global challenges—can facilitate the activation of immovable cultural heritage and enhance quality of life in community. Based on a plural analysis of 18 cases from Slovenia and abroad, gathered through semi-structured questionnaires with cultural heritage experts, we identify correlations between strong levels of new localism fac-tors and strong elements of immovable cultural heritage that are linked to quality of life. The data also highlight the critical role of social factors—such as participation and social integration—in enabling the long-term development of local communi-ties through heritage-based practices. We note that high intensities in cases where we have the presence of multiple new localism factors create synergistic effects that are supported by local communities, while dominance of a single factor often leads to an overemphasis of localism trend or particular interests of main actors on locations.
Keywords: immovable cultural heritage; Kakovost življenja; Kulturna dediščina; nepremična kulturna dediščina; new localism; novi lokalizem; quality of life; Slovenia